2018
DOI: 10.1186/s13075-018-1686-9
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound of the skin in systemic sclerosis: an exploratory study to examine correlation with disease activity and to define the minimally detectable difference

Abstract: BackgroundThickened skin is a major clinical feature in patients with systemic sclerosis (SSc). We investigated changes of skin thickness in patients with SSc using both high frequency ultrasound (HFU) and the modified Rodnan skin score (mRSS) to evaluate the feasibility of application of HFU in skin involvement and the relationship between HFU and clinical profiles.MethodsWe recruited 31 consecutive patients with SSc and 31 age-matched and sex-matched healthy controls in this prospective, cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
4
41
1
1
Order By: Relevance
“…In terms of sensitivity, prior reports have shown the advantage of ultrasound in detecting subclinical skin thickening which was not perceivable by physical examination [10,11]. In the current study, we further revealed that patients with exactly the same mRSS could have markedly different ultrasound-measured skin thickness and skin stiffness.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In terms of sensitivity, prior reports have shown the advantage of ultrasound in detecting subclinical skin thickening which was not perceivable by physical examination [10,11]. In the current study, we further revealed that patients with exactly the same mRSS could have markedly different ultrasound-measured skin thickness and skin stiffness.…”
Section: Discussionsupporting
confidence: 58%
“…Skin ultrasound has been recognized as a valuable supplement to clinical skin assessment in SSc. First, subtle skin thickening was detectable by ultrasound even in the skin areas with a normal mRSS [10,11]. Second, ultrasound was more sensitive to treatment-induced skin changes than clinical skin scores [12].…”
Section: Introductionmentioning
confidence: 99%
“…With a progress in diagnostic imaging, researchers focused their interest on the applicability of ultrasonography for the evaluation of the severity and extent of skin fibrosis in SSc [13,14]. The ultrasound elastography is an ultrasonographic technique suitable for the quantification of skin fibrosis, indicating not the thickening of the skin, but its strain-a parameter, which can be considered as a more detailed marker of a change of the skin structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by the availability of ultrasound machines equipped with higher frequency probes (i.e. [18][19][20][21][22][23][24][25][26][27][28][29][30], which allowed for a more widespread use of ultrasound for the study of skin thickness. In fact, these machines provide a better visualization of superficial skin structures, including epidermis, dermis and subcutaneous fat tissue, thus making it possible to make quantitative (i.e.…”
Section: Skin High-frequency Ultrasoundmentioning
confidence: 99%